Laser ablation behavior and mechanism of Cf/SiC–ZrC ultra-high temperature ceramic matrix composite prepared by PIP method. Issue 16 (15th August 2021) - Liu, Rongjun; Liu, Xingyu; Wang, Yanfei; Miao, Huaming; Song, Changqing; Qi, Gongjin; Wan, Fan
Abstract: Cf /SiC–ZrC ultra-high temperature ceramic matrix composites prepared by precursor impregnation and pyrolysis (PIP) method were exposed to laser with energy density of kW level and the ablation behavior and mechanism were investigated. The results show that under different ablation times, the composites exhibited similar ablation region divisions, namely, central ablation pit, ablation transition zone, oxidation zone and non-ablated zone. Sample subjected to laser ablation of 5 s has the largest linear ablation rate of 0.0946 mm/s, which decreased to 0.0748 mm/s for 10 s ablation sample, and after that increased to 0.0876 mm/s for 15 s ablation sample. Under high-energy laser ablation, ZrO2 was the main anti-ablative component among the oxides formed by the oxidation of the matrix, which underwent morphology changes from sheets, fragments to micro and nano particles. Dense structure and continuous anti-ablation layer with high melting point components are the key factors to improve the anti-laser ablation performance of materials.